PENGEMBANGAN BAHAN AJAR KEBENCANAAN MENUJU RESILIENSI SOSIAL DAN MITIGASI BENCANA MAHASISWA UIN TULUNGAGUNG - Pratama, Hendra; Setiawan, Bagus (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The development of disaster teaching materials integrates a multidisciplinary approach, including disaster technology, social science, and environmental sustainability. This approach aims to provide a holistic and applicable learning experience. In addition, the teaching materials utilise project-based learning methods, simulations and case studies to enhance students' capacity to analyse risks and design innovative solutions. Research shows that these methods are effective in building practical skills while raising collective awareness on the importance of a culture of disaster preparedness. Disaster simulations are also implemented as part of the learning process to provide practical experience to students. provide practical experience to students. Through these simulations, students can practice various mitigation and emergency response techniques, such as evacuation and the use of first aid equipment. The results showed that this practical training improved students' understanding of disasters as well as their confidence in dealing with emergency situations. Thus, the development of printed teaching materials accompanied by disaster simulations is expected to build a disaster-aware culture among students and strengthen their capacity to deal with disaster risks in the future.